Simplify the following expression:
START_INT\sqrt{RADICAL_TOTAL}
.
First, try to factor a perfect square out of the radical.
= START_INT\sqrt{RADICAL_TOTAL}
= START_INT\sqrt{pow( RADICAL_INT , 2 ) \cdot RADICAL_PRIME}
Separate the radical and simplify.
= START_INT\sqrt{pow( RADICAL_INT , 2 )} \cdot \sqrt{RADICAL_PRIME}
= START_INT \cdot RADICAL_INT \cdot \sqrt{RADICAL_PRIME}
= START_INT * RADICAL_INT\sqrt{RADICAL_PRIME}
Simplify the following expression:
START_INT\sqrt{RADICAL_TOTAL}
.
There are no perfect-square factors of RADICAL_TOTAL.
Thus, the expression is already in its most simplified form.
= START_INT\sqrt{RADICAL_TOTAL}